Exploring vocabulary growth through songs: an in-depth interview of Malaysian undergraduate students - Meganathan, Pavani Malaa; Satyanarayana, Shaila Devi; Arumugam, Nalini (Universiti Putra Malaysia, 2024)
This study investigates the perceptions of Malaysian undergraduate students regarding the use of English songs as a tool for vocabulary acquisition. Through in-depth interviews with five undergraduate students in Malaysia, the study examines their experiences, insights, and reflections on utilising English songs to expand their vocabulary. Four prominent themes emerged from the analysis: subconscious word learning, learning of pronunciation and accent, vocabulary retention, and exposure to authentic English words. The results reveal that while listening to English songs undergraduate students in Malaysia improve their English language by learning new words, accent and improving pronunciation. Learners benefit from the autonomy to choose strategies they deem suitable for their learning, while also benefiting from teachers' guidance on various strategies to employ. The study concludes that there is a growing preference for engaging approaches such as using English songs, and providing students with an enjoyable and immersive way to learn vocabulary